Pengembangan Modul Pembelajaran PAI Dan Budi Pekerti Dalam Menunjang Pembelajaran Daring Di SD Negeri 59 Payakumbuh - Riza Novira; Supriadi (Arus Jurnal Pendidikan, 2022)
This research was motivated by the lack of availability of Islamic Religious Education and Moral Education textbooks in schools. And so far the school still does not have a supply of learning resources in the form of modules. Some learning resources are still limited with simple teaching materials. Especially during the Covid-19 pandemic, there have been several problems with distance learning. The teacher as an educator is required to be able to create teaching materials according to the conditions of students at this time. This study aims to develop teaching materials in the form of modules on PAI and Budi Pekerti subjects in the fourth grade of elementary school. As well as to determine the impact of its use on improving student learning outcomes in grade IV SD Negeri 59 Payakumbuh. The type of research used is research and development (R & D) using the ADDIE model. The stages of development are as follows: 1) Analysis Stage, 2) Design Stage, 3) Development Stage, 4) Implementation Stage, 5) Evaluation Stage. The results showed that (1) this development research produced a product in the form of PAI and Budi Pekerti learning modules which aimed to increase the learning motivation of fourth grade students at SD Negeri 59 Payakumbuh (2) The results of research and development of PAI and Budi Pekerti learning modules met the valid criteria with the percentage of test results by material experts is 4.00, module design experts are 4.57 media design experts are 4.46, and subject teachers are 94.71 (3) There is a significant increase in student learning outcomes. The results showed that (1) this development research produced a product in the form of PAI and Budi Pekerti learning modules which aimed to increase the learning motivation of fourth grade students at SD Negeri 59 Payakumbuh (2) The results of research and development of PAI and Budi Pekerti learning modules met the valid criteria with the percentage of test results by material, design and language experts obtained a moderate value of 1 or 7.31%, a high score of 12 or 58.53%, and a very high score of 16 or 39.02% with valid interpretations, and high grade subject teachers 15 or 28.84%, and a very high value of 37 or 71.15% with a very practical interpretation. (3) There is a significant increase in student learning outcomes. The average pre-test value of the experimental class was 70.15 and the average pre-test of the control class was 67.69. While the post-test value of the experimental class was 88.92 and the post-test value of the control class was 83.38. The results of the validity test using SPSS show that the value of Cronbach's Alpha produced is 0.835 which is greater than the alpha value of 0.05. The results of the practicality test show that the resulting Cronbach's Alpha value is 0.852, which is greater than the alpha value of 0.05. So that it can be interpreted that the practicality of this module (product) in the view of the PAI teacher has a very high level of reliability. The results obtained by students after using the developmental teaching materials have increased, the average value obtained before using the development product is: the experimental class 70.15 and the control class 67.69. After using the product development results, the scores obtained by the students increased to: the experimental class 88.92 and the control class 83.38.